Pengaruh Viral Marketing dan Elektronic Word Of Mouth Terhadap Keputusan Pembelian pada UMKM Seblak Teh Windy Melalui Followers Tiktok - Nenden Kusmawati; Citra Savitri; Syifa Pramudita Faddila (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The internet has been proven to be able to make it easier for someone to get information and facilitate communication between one person and another. The ease of information spreading on the internet is also accompanied by the existence of social media which is used as a promotional medium by business actors, one of which is Seblak Teh Windy. The aim of this research was to find out whether viral marketing and electronic word of mouth have an influence on purchasing decisions for Seblak Teh Windy. This research uses a quantitative approach, descriptive and verification approach. The population studied was based on Tiktok Followers @seblaktehwindy16 in November 2023, which numbered around 553,600 and the number of samples used was 400 respondents. The sampling technique used in the research was non-probability sampling using purposive sampling. The results of this research state that Viral Marketing and Electronic Word of Mouth are related to purchasing decisions. It can be concluded that Viral Marketing and Electronic word of mouth have a significant influence on the decision to purchase Seblak Teh Windy.